1987
DOI: 10.1112/jlms/s2-36.1.95
|View full text |Cite
|
Sign up to set email alerts
|

The Bloch Constant of Bounded Analytic Functions

Abstract: In this work we solve the extremal problem of characterizing all bounded analytic functions f: Δ → C (where Δ is the open unit disk) for which the Bloch constant βf = sup{(1−|z|2)|f′(z)|: z ε Δ is a bound. Normalizing, we study f: Δ → Δ with βf = 1. We show that these are precisely the conformal automorphisms of Δ together with those functions whose zeros form an infinite sequence (zn)nεN such that lim supn→∞|g(zn)|Πk≠nzn−zk1−znzk=1, where g is the non‐vanishing function such that f/g is a Blaschke product. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It is well known that harmonic functions from Hardy class can be represented as Poisson integral u(x) = S P (x, ζ)dµ(ζ), x ∈ B n where P (x, ζ) = 1 − |x| 2 |x − ζ| n , x ∈ B n , ζ ∈ S is Poisson kernel and µ is complex Borel measure. In the case p > 1 this measure is absolutely continuous with respect to σ and dµ(ζ) = f (ζ)dσ.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that harmonic functions from Hardy class can be represented as Poisson integral u(x) = S P (x, ζ)dµ(ζ), x ∈ B n where P (x, ζ) = 1 − |x| 2 |x − ζ| n , x ∈ B n , ζ ∈ S is Poisson kernel and µ is complex Borel measure. In the case p > 1 this measure is absolutely continuous with respect to σ and dµ(ζ) = f (ζ)dσ.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…We refer to [2,Theorem 1] for the proof of (1.4). In the same paper Colonna proved that, if w is a harmonic mapping of the unit disk into itself, then there hold the following sharp inequality (1.5) β w 4 π .…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…The techniques used here are somewhat different from those of [3]. There, the main result characterizes the extremal functions in terms of the distribution of their zeros, and at the same time provides a recipe for constructing examples.…”
Section: Introductionmentioning
confidence: 99%
“…In [3] it is observed that the Bloch constant of a bounded analytic function never exceeds its sup-norm, and those functions / for which ßf = suP|zi<i l/(z)l are characterized. Normalizing, we may consider bounded functions as having image in A and the result becomes the following: where g is a nonvanishing factor of fi such that fi/g is a Blaschke product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation